BRAND ACTIVATION TERHADAP INOVASI “WE BRING STUDIO TO YOU BY VIVREE PHOTOGRAPHY” - Jonathan Jamian Eliezer; Hutomo Budi (Universitas Ciputra Surabaya, 2021)
The purpose of this study is to become a reference for the literature review collected by authors regarding branding, innovation on problems, brand activation, and suitable media for Vivree to carry out brand activation on their innovations. This research uses literature review method of national and international books and journals. The results of this study also show that branding is a value added that usually solves problems for consumers in a business that we usually call innovation. Brand activation is also a way for an innovation to be accepted in the market by using social media which is currently in demand by many people, and if all has been done it is possible for an innovation to survive with its commitment. Therefore, this study shows that the importance of branding can be extended if brand activation is carried out with the right social media. Keywords: Branding, Innovation, Brand activation, Social Media, Sustainable